All About Extraterrestrial Life - Ross, Alena, author 648377 (Delhi, India : University Publication : World Technologies, 2012)
Extraterrestrial life (from the Latin words : extra ("beyond", or "not of") and terrestris ("of or belonging to Earth")) is defined as life that does not originate from Earth . Possible forms of extraterrestrial life range from simple bacteria-like organisms to sapient beings far more advanced than humans. It is unknown whether any such forms of life exist or ever existed. The development and testing of theories about extraterrestrial life is known as exobiology, xenobiology or astrobiology, the term astrobiology however also covers the study of life on Earth, viewed in its astronomical context. Various claims have been made for evidence of extraterrestrial life, such as those listed in a 2006 New Scientist article, which the magazine describes as "hints" rather than proof. A less direct argument for the existence of extraterrestrial life relies on the vast size of the observable Universe. According to this argument, endorsed by scientists such as Carl Sagan and Stephen Hawking, it would be improbable for life nor to exist somewhere other than Earth and its spacecrafts. One possibility is that life has emerged independently at many places throughout the Universe. Another possibility is panspermia or exogenesis, in which life would have spread between habitable planets. These two hypotheses are not necessarily mutually exclusive.